Pembelajaran Berkarakteristik Inovatif Abad 21 Pada Materi Bumi Dan Antariksa Dengan Model Pembelajaran Project Based Learning Di Smk Negeri 1 Adiwerna - Tanti Tanti; Sutji Muljani (Cakrawala: Jurnal Pendidikan, 2022)
Students are already active in learning, but many forget the material that has been given. When giving opinions, they are less motivated to learn. 21st century skills are still very low, this can be seen when face-to-face learning is limited. The reason is that many students cannot absorb subjects well, the limitations of learning are carried out remotely. This article aims to describe the improvement of 21st century skills due to the implementation of project-based learning. This article is an explanation based on real events in learning. The research subjects were all students of class X SMK Negeri 1 Adiwerna, totaling 36 people. Student learning outcomes on average 82% where this value already meets the criteria of classical completeness, motivation increases from every face-to-face meeting. Students are able to express opinions, collaborate in concluding the results of discussions, increase critical thinking power as evidenced by the HOTS questions given by the teacher that can be answered properly.